2019
DOI: 10.17221/222/2017-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of some nutritional parameters of the tomato fruit during the harvesting stages

Abstract: The main purpose of this study was to highlight the nutraceutical value of the tomato fruit for five hybrids recently introduced in culture, during the harvesting phases: mature green, half ripen and full ripen: ‘Antalya’, ‘Cemil’, ‘Lorely’, ‘Tiger’ and ‘Sacher’. They differentiate because of their size and fruit colour. The parameters to be followed for each harvest phase were: the chlorophyll a and b content, the total carotenes, the soluble substance, vitamin C, the titratable acidity, and also a maturity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In this regard, our results indicate that tomato fruit decreased along without BAP application under heat stress, while application of 600 ppm BAP altered the impact of exceeded temperatures. The results are similar to those reported by other researchers who showed a variation in fruit quality and quantity depending on the cultivated variety and environmental conditions [62][63][64][65]. High temperature conditions could result in an increase in the TSS content in tomato fruits [66].…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, our results indicate that tomato fruit decreased along without BAP application under heat stress, while application of 600 ppm BAP altered the impact of exceeded temperatures. The results are similar to those reported by other researchers who showed a variation in fruit quality and quantity depending on the cultivated variety and environmental conditions [62][63][64][65]. High temperature conditions could result in an increase in the TSS content in tomato fruits [66].…”
Section: Discussionsupporting
confidence: 91%
“…Chlorophyll b had high values at Sacher F1 hybrid, in the green fruit phase, and at Tiger F1 and Sacher F1 hybrids in the rose fruit phase (Table 2). Similar results were reported by Soare et al (2019) in a conventional tomato crop. Consequently, it can be stated that the organic culture system has directly influenced the accumulation of chlorophyll a and b in tomato fruits, a statement also supported by Khan et al (2017), who observed that chlorophyll a and b in tomato fruits can be significantly larger in organically fertilized plants.…”
Section: Mineral Contentsupporting
confidence: 90%
“…Identifying tomato cultivars with high nutritional value is a useful approach that is taken into account when selecting those that have beneficial properties for better health. During the ripening process of tomato fruits, a series of quantitative and qualitative changes take place, which influence the aroma and volatile profiles of tomato taste (Soare et al, 2019). However, the increase or decrease in nutrients in tomatoes can be influenced by genotype, climate and soil conditions and the farming system.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Duma et al ( 32 ) showed that when comparing fruits mass and TI, it is observed that higher TI is for smaller or bigger tomatoes. Experiments of Rodica et al ( 23 ) showed that cherry and brownish red-colored tomatoes contain more soluble solids. In this study, it is underlined that quantity of the organic compounds determining the fruit taste depends on the yield of the cultivar.…”
Section: Discussionmentioning
confidence: 99%